eBooks for Libraries and Patrons: Two Years of Experience - Rosy, Richard L. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
A little over two years ago, netLibrary defined its primary mission to encompass a singular focus on developing and offering library-centric solutions for organizing, hosting, and serving digital learning content in ways that integrated with the mission and methods of libraries. Today, netLibrary provides thousands of academic, public, government, corporate, special and school libraries with access to digital versions of monograph content they deem of particular value to their patrons.